TRANSFORMASI SUPERVISI SEKOLAH MELALUI NILAI-NILAI MANAJEMEN ISLAM: IMPLIKASINYA TERHADAP BUDAYA ORGANISASI DAN EFEKTIFITAS PENDIDIKAN - Halifah Halifah (STKIP Pesisir Selatan, 2026)
jective: This study explores the transformation of academic supervision through the internalization of Islamic management values and its implications for organizational culture and educational effectiveness in modern Islamic boarding schools, which stand between traditional pesantren values and contemporary educational management demands. Methods: This research employed a qualitative approach with an interpretive case study design. Data were collected through document analysis, including supervision policies, academic guidelines, evaluation instruments, supervision reports, follow-up action plans, and meeting minutes related to supervisory practices. The documents were analyzed using reflective thematic analysis to identify patterns of meaning and value dynamics shaping academic supervision at the institutional level. Results: The findings reveal four main themes: a shift from administrative compliance to institutional trust (amanah), shura as a dialogic yet negotiated supervisory practice, ‘adl as ethical justice between standardization and contextual sensitivity, and ihsan as an orientation toward sustainable quality improvement accompanied by institutional tension. Academic supervision thus emerges not merely as a technical procedure, but as a social and cultural process shaped by value negotiation, power relations, and organizational identity. Novelty: This study conceptualizes Islamic management values not only as normative leadership principles, but also as socially constructed practices embedded in supervisory documents and organizational culture.